AGENSI LAKI-LAKI DALAM PENCEGAHAN KEKERASAN BERBASIS GENDER DALAM KELUARGA: STUDI KELUARGA DESA JETIS, SAPTOSARI, GUNUNGKIDUL - Khairun Nisa; Muhammad Mukhlis Ardianto (Kopertais Wilayah III Yogyakarta, 2022)
The majority of men are perpetrators of gender-based violence in the family. Meanwhile, men who are not perpetrators of violence, often choose to be the silent majority, because they consider violence to be in the private sphere. Involving men in the discourse and practice of gender-aware education is expected to change the perspective and attitude of men in seeing women. This is done to decide and reduce the number of violence against women and children. This study focuses on the agency of men in efforts to prevent gender-based violence in the family and to achieve gender justice in the family. Using descriptive qualitative methods with observation and interview models, the resource persons were taken from participants who took part in the father's class program and community facilitators from Rifka Aniisa WCC. This study shows that the process of building agent awareness begins through the reinterpretation of religious texts with religious leaders. This interpretation provides new understanding to the participants in the father class discussion regarding relationships with partners based on monotheism. Practical awareness is achieved by agents through assertive communication with partners. Agents reflect on material learned in class with a partner. The results of these reflections become the basis for producing a just social system in the family and society. Keyword: Gender Equality and Justice, Rifka Annisa, Agen and Strucutre